ಮೈಸೂರು ವಿಶ್ವವಿದ್ಯಾಲಯ ವಿಶ್ವಕೋಶ : ಕನ್ನಡ ವಿಶ್ವಕೋಶ - ಸಂಪುಟ ೨ - (:unkn) unknown (University of Mysore)
This Encyclopedia provide information about various Scientific aspects of various plants and vegetables
Mysuru Vishwavidyalaya Kannada Vishwakosha Vol – 2
Keywords: Kannada; Encyclopedia; Kannada